Uji Skrining Fitokimia Menggunakna Daun Pegagan (Centella Asitica) Untuk Mengidentifikasi Senyawa Alkaloid, Flavonoid, dan Saponin - Syahrul Muflih Harahap; Ahmad Baihaqi Ananda El Rawy; Muhammad Ibnu Sina (International Forum of Researchers and Lecturers, 2024)
As a tropical country, Indonesia has many types of biodiversity, including plants that are spread throughout Indonesia, approximately as many as 40,000 species with 7,500 species of which can be used as medicinal plants which are applied for medical needs and biological and chemical research. One of the topics discussed in this journal is the gotu kola leaf, known as the Latin name (centella asiatica). This plant contains tannins, flavonoids, vitamin A and vitamin C with various properties including accelerating the wound healing process, other benefits such as improving brain and nerve function. It should be noted that this efficacy is due to the presence of secondary metabolites in the gotu kola leaf and to find out, alkaloid, flavonoid, and saponin tests were carried out using dried gotu kola leaves and then divided into two bottles of 200 ml of methanol and N-hexane solution and then macerated for 3 days. . After the maceration process is complete, a thick extract of gotu kola leaves is produced and then continued with testing for alkaloids, flavonoids, and saponins which will later get results that aim to be the first step to determine secondary metabolite compounds and be useful as information on the utilization of the efficacy of gotu kola leaves as well as research in biology and chemistry.